PHYSICO-CHEMISTRY OF GEOPHAGIC SOILS INGESTED TO RELIEF NAUSEA AND VOMITING DURING PREGNANCY - Diko, M L; Siewe épse Diko, D N (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Nausea and vomiting during pregnancy (NVP) is one of the most common symptoms experienced by most women during their first trimester of pregnancy. For some of these women, especially the more tribally and culturally oriented ones, soil ingestion is one of the remedies used to curb NVP. The aim of this study was to physico-chemically characterise selected geophagic soils from Cameroon and South Africa, ingested for the relief of NVP and to appraise their ability to meet the needs of geophagic individuals. Materials and Methods: Thirteen geophagic soil samples (6 from Cameroon and 7 from South Africa) were obtained from traditional mine sites and physico-chemically characterized. The following tests were conducted; particle size distribution (PSD), liquid limit (LL), plastic limit (PL), plasticity index, soil pH and electrical conductivity (EC). Results: The samples were texturally classified as silt loam, of medium to high plasticity with normal to active swelling potentials. The samples were generally acidic (pH of 3.1 – 6.1) with low EC (average of 92.71µS/cm). Conclusion: Based on soil consistency limits and pH, the samples were found to be suitable for use as remedy for NVP with soils from Cameroon displaying the most optimum properties.